ASEAN at the Crossroads of US-China Rivalry: The Role of Majority Voting and the Introduction of a Permanent Secretary-General - Lee, Brice Tseen Fu; Sims, Juan Pablo (International Journal of Law and Public Policy (IJLAPP), 2024)
This paper examines ASEAN's need for structural reform amidst the US-China rivalry, highlighting the limitations of its consensus approach during crises. It proposes majority voting as an emergency measure and advocates for a Permanent Secretary-General position, ensuring consistent leadership. The analysis balances the benefits and challenges of these reforms, emphasizing the necessity for ASEAN to evolve while maintaining its core values, ensuring relevance and unity in addressing major geopolitical challenges.